Tipe Pengungkapan Lingkungan dalam Laporan Tahunan Perusahaan Publik di Indonesia - Utpala Rani; Octavia Lhaksmi Pramudyastuti (Wahana Riset Akuntansi, 2021)
This descriptive study explores the types of pro-environmental behavior that public companies in Indonesia disclose in their annual reports. In general, environmental disclosure is one of the company's channels to send signals to stakeholders about the company's attitude and commitment to environmental protection. In this study, the types of environmental disclosure for 160 public companies listed on the IDX were identified by content analysis. The results show that most of the sample companies committed greenwashing for the disclosure of their pro-environmental commitments in the annual reports. This indicates that environmental disclosure by public companies in Indonesia tends to be symbolic and oriented solely to regulatory compliance.Keywords: Environmental Disclosure; Pro-Environment Behavior; Greenwashing; Public Company.